PEMANFAATAN INTEGRATED LIBRARY SYSTEM (INLISLITE) DALAM MENINGKATKAN LAYANAN DI DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN BADUNG - Ni Made Dina Witari; Ni Putu Premierita Haryanti; Putu Oka Sujana (D3 Perpustakaan FISIP UNUD, 2025)
This inquiry endeavors to explore the deployment of the library automation mechanism via Inlislite in augmenting service efficacy at the Archives and Library Office of Badung Regency, while also delineating the impediments encountered throughout its operationalization. Inlislite is a software suite conceived by the National Library of the Republic of Indonesia to facilitate cohesive and digitized library administration. The study adopts a qualitative-descriptive paradigm, employing data elicitation techniques such as immersive observation, in-depth interviews, and archival documentation. Key informants encompass the head of the institution, technical and public service librarians, along with regular library patrons. The investigation uncovers that Inlislite is harnessed in a multitude of functions, including circulation processes, user account regulation, catalog development, report generation, and collection retrieval through the OPAC (Online Public Access Catalog). The integration of this system has imparted advantageous transformations to the performance of the institution. Nevertheless, certain constraints persist, notably intermittent network and server malfunctions, the absence of real-time interactive features between librarians and users, and insufficient outreach or dissemination efforts to the wider community.